Supplementary Figure 5 from Preclinical Study of a Biparatopic METxMET Antibody–Drug Conjugate, REGN5093-M114, Overcomes MET-driven Acquired Resistance to EGFR TKIs in EGFR-mutant NSCLC - Seung Yeon Oh (15051017) (2025)
(A-B) Apoptosis level was measured after incubated with drugs for 48 hours. YU1089 and HCC827 AR cells were treated with osimertinib, capmatinib or tepotinib at a concentration of 100nM, Control Ab-M114 at 1 µg/ml or REGN5093-M114 at 1 µg/ml.